A Novel Proxy for Tracking the Provenance of Dust Based on Paired E1'‐Peroxy Paramagnetic Defect Centers in Fine‐Grained Quartz. Issue 10 (25th May 2022) - Dave, Aditi K.; Timar‐Gabor, Alida; Kabacińska, Zuzanna; Scardia, Giancarlo; Safaraliev, Nosir; Nigmatova, Saida; Fitzsimmons, Kathryn E.
Abstract: Crystal lattice defects in quartz have long been exploited for age determination, yet also show potential for sediment provenance studies. Here, we introduce a novel method for tracking aeolian dust provenance by utilizing the natural accumulation of E1 ' and peroxy defect centers in quartz. Our approach is based on the previously observed premise that E1 ' and peroxy centers arise from Frenkel defect pairs, and that their concentration increases with the age of the quartz‐bearing source rock. We propose that these defect centers can be utilized as a characteristic feature of the source rock and consequently, for fingerprinting sediments derived from it. We successfully apply our new protocol to distinguish fine‐grained quartz extracted from loess deposits from two regions in Central Asia which are known to derive from different source material of differing age. Our method offers strong potential for identifying variability in source, both spatially and through time down sedimentary sequences. Plain Language Summary: Identifying the origins of dust deposits allows us to reconstruct sediment transport pathways which are essential for understanding past atmospheric circulation patterns. Here, we propose to exploit the characteristics of two naturally occurring defect centers in crystalline quartz, the E1 ', and peroxy centers, as a means to distinguish sediment deriving from different origins. These centers occur as pairs and are hypothesized to increase with the age of the quartz‐bearing rock. By this logic, the E1 ' and peroxy centers can be used to determine the lithic origins of sedimentary quartz in a similar way to detrital zircon‐based provenance techniques, while analyzing a more ubiquitous mineral (quartz). We apply our approach, which uses a simplified protocol for measurement in contrast to earlier studies, to successfully distinguish between loess (wind‐blown dust deposits) from two different basins in Central Asia. Our new method holds great potential in its application to loess sequences as well as other sedimentary archives. Key Points: New sediment provenance tool exploits E1 ' and peroxy paramagnetic defects in quartz New proxy successfully differentiates quartz in loess from two different basins in Central Asia Potential applications for identifying climate‐driven source change through time in loess and other sedimentary sequences